International Human Rights Analysis of Israeli War Crimes Against Palestine Reviewed from International Criminal Law - Putri Ramadhani; Tika Puspita Sari; Jada Bashira (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The armed conflict between Israel and Palestine is one of the longest-running humanitarian crises of the 21st century and continues to leave deep scars on human civilization. This study examines violations of international human rights law committed during this conflict, including the bombing of civilian areas, massacres, systematic destruction of property, genocide against ethnic groups, and the destruction of vital facilities such as hospitals, schools, and civilian infrastructure. This article employs a normative legal research methodology with a comparative and analytical approach to relevant international legal instruments, particularly the 1998 Rome Statute, the 1949 Geneva Conventions and their Additional Protocols, and the jurisprudence of the International Criminal Court. The article analyzes the chronology of the conflict from its historical roots in 1948 to its most recent escalation in 2023–2024, which claimed the lives of tens of thousands of Palestinian civilians. The study concludes with strong indications of violations of fundamental principles of international humanitarian law, including distinction, proportionality, and precaution. However, efforts to enforce international criminal law through the International Criminal Court face fundamental structural obstacles, including lack of jurisdiction over non-member states, veto power in the UN Security Council, and impunity fostered by global geopolitics. This article argues that the failure to resolve these conflicts stems not only from legal weaknesses but also from the inability of international politics to prioritize justice over the strategic interests of major powers.